Group formation in a pandemic world - Tan, Janssen Guan Rong (Nanyang Technological University, 2022)
Universities have been relying on student project work as a cornerstone to the educational paradigm for many years. In addition, in the years that university education has been around, most classes have been in person. However, with the emergence of the pandemic since 2020, we have seen a shift to an online classroom setting, which has had an adverse effect in terms of the social relationships formed. This has provided a unique context to the group formation problem, where traditional approaches to group formation might no longer be effective. The project looks to provide the foundation to a new paradigm in the solving of the group formation problem. To do so, we reviewed several existing solutions and approaches to the group formation problem, as well as other studies that relate to group formation in an online setting. The result is the formation of a student group matching algorithm that optimises a metric that looks to consider the real- world situations and problems that students face in a pandemic world. The algorithm is then operationalised in a group matching web application. Finally, we conclude the project by highlighting future enhancements to integrate the solution to existing operations and infrastructure of universities.